Hemostasis of parenchyma using adhesive plastics - del Campo, Alberto; Briano, Mario A; Gómez Fossati, Carlos; Martinello, Enver (Cirugía del Uruguay, 2020)
In the last decade, the study of polymeric materials with adhesive properties has begun, with the aim of complementing or replacing the classic surgical haemostasis and suture methods.